Pengembangan Modul Quick Math Berbasis Mobile Learning sebagai Penunjang Pembelajaran Matematika di SMA - C. Cecep; Anwar Mutaqin; Aan Subhan Pamungkas (IKIP Mataram, 2019)
[Title: Development of Quick Math Module Based on Mobile Learning as a Support for Mathematics Learning in High School]. Learning resources is a very important component of the learning process. One of the learning resources that can be utilized independently is the module. The purpose of this research is to develop the Quick Math module and evaluate the feasibility of the module. The development model used is the ADDIE model namely analysis, design, development, implementation and evaluation. The subject in this study was 15 students consisting of low, moderate and high-performance level and 6 teachers at SMA Negeri 2 Kota Serang. The instruments used to collect data in this research consist of expert validation questionnaire (content and media), Teacher and student response questionnaire. Based on data analysis results, obtained the score of the content material about 86.4% with a very feasible category, media experts about 88% with very feasible category, teacher response of 92% with very good category and student response of 88.39% with the very good category. Based on the data analysis it can be concluded that the Quick Math module is developed feasible to be used as a learning resource in accordance with the demands of the 2013 curriculum. This app makes it easy for students to access flexible learning resources wherever and whenever.